PENGEMBANGAN E-MODULE BERBASIS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) UNTUK PESERTA DIDIK KELAS VII SMP/MTs - Syamsul Haj (Jurnal Edukasi dan Penelitian Matematika, 2022)
The goals of this research to determine the characteristics of the mathematical e-module based on Realistic Mathematics Education for Class VII SMP/MTs students that are valid and practical in supporting the success of the learning mathematics. This E-Module uses the Plomp development model which consists of 2 stages, namely the preliminary research and prototyping phase. The subjects of this research were 9 students of class VII MTs PP Nurul Islam Gunung Toar. The instruments used are validation sheets and questionnaires for teacher and student. In this research, a valid and practical mathematical e-module was obtained. The e-module is valid with 86.79% results in the very valid category. A The results of the questionnaire for teacher responses obtained a practicality value of 90.00% with a very practical category. As for the student questionnaire, the practicality value of 92.94% was obtained in the very practical category. Keywords– E-module, Realistic Mathematics Education, Valid, Practical